PENGGUNAAN PROGRAM ISPRING 7.0 DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V - Noer, Juanda; Kresnadi, Hery; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problem in this study is whether the use of Ispring 7.0 program can improve the learning outcomes of students of grade V Primary School 17 Pontianak City. The research method used is descriptive with the form of action research class. Research subjects are teachers as researchers and students of class V which amounted to 36 people. The procedure consists of planning, implementation, observation and reflection. The data collected is the data of teachers' ability to design and implement learning, and student learning outcomes. Data collection techniques use document observation and scrutiny. The data collection tool uses observation sheet and student learning result document. Data analysis using average calculation. The study was conducted in 2 cycles. The result of the research is the average score of teacher's ability to design the learning in the first cycle of 3.75 and on the second cycle of 3.90. The average score of teachers' ability to implement the learning in the first cycle of 3.67 and on the second cycle of 4.00. Average Score Student learning outcomes in cycle I of 76.00 and on the second cycle of 95.61. Thus, the use of Ispring 7.0 program can improve student learning outcomes. Keywords: Ispring 7.0, Mathematics, Learning outcomes